Back Cover Image. Issue 9 (14th October 2019) - Jiang, Huan; Tang, Qi; Jiang, Yan; Li, Ningshan; Tang, Xuefeng; Xia, Hongmei
Abstract : The back cover image is based on the Original Article Echocardiographic and Pathomorphological Features in Fetuses with Ductal‐Dependent Congenital Heart Diseases by Hongmei Xia et al., https://doi.org/10.1111/echo.14452 .